2018
DOI: 10.1021/acs.inorgchem.8b02800
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, Magnetic, and Theoretical Characterization of (NH4)4UF8, a Simple Molecular Uranium(IV) Fluoride

Abstract: The simple system of tetraammonium octafluorouranate is employed to derive a fundamental understanding of the uranium–fluorine interaction. The structure is composed of isolated molecules, enabling a detailed examination of the U4+ (f 2) ion. Characterization of single-crystals by X-ray diffraction, absorption spectroscopy, and magnetic analysis up to 45 T is combined with extensive theoretical treatment by CASSCF. The influence of different active spaces and representations of the structure is examined in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 74 publications
(111 reference statements)
3
36
0
Order By: Relevance
“…Key elements within QTAIM were extracted such as the electron density, delocalization indices, and energy densities at the interatomic region (bond critical point, BCP) which have been employed previously for this aim. [40][41][42][43][44][45][46][47][48] The covalency was analyzed, on one hand, by changes in the concentration of the electron density at the BCP along with changes in the delocalization indices. On the other hand, energy densities show the polarization of the covalent bond by looking at the ratios between potential [V(r)] and kinetic [G(r)] energy densities, which for partial covalent bonds lie in between values of 1 and 2.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Key elements within QTAIM were extracted such as the electron density, delocalization indices, and energy densities at the interatomic region (bond critical point, BCP) which have been employed previously for this aim. [40][41][42][43][44][45][46][47][48] The covalency was analyzed, on one hand, by changes in the concentration of the electron density at the BCP along with changes in the delocalization indices. On the other hand, energy densities show the polarization of the covalent bond by looking at the ratios between potential [V(r)] and kinetic [G(r)] energy densities, which for partial covalent bonds lie in between values of 1 and 2.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Based on previous studies where the nature of bonding interactions of fblock complexes has been shown that bonds are not formally covalent, but rather partially covalent. 46,47,93 A partial covalent bond implies positive values for the Laplacian of the electron density, Vr(r), and negative values for total energy densities, H(r). Here, the term "covalency" refers to the metal-ligand interaction needed to experience orbital overlap, which is re-ected by the buildup of electron density [r(r)] in the interatomic region.…”
Section: Bonding Analysismentioning
confidence: 99%
“…[3] In recent years single-crystal structure determinations of ternary fluoridometallates(IV) have mainly been carried out for Th and U compounds, whereas such studies and thus detailed structural parameters for compounds of the transuranium elements are lacking. [3][4][5][6][7] For the latter, usually only data obtained from powder diffraction studies have been reported, with the exception of a few single-crystal structure determinations. [1,2,[8][9][10][11][12][13] The coordination number of the actinide atom in ternary fluoridometallates(IV) is usually nine, with a tricapped-trigonal prismatic arrangement of the fluorido ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,[8][9][10][11][12][13] The coordination number of the actinide atom in ternary fluoridometallates(IV) is usually nine, with a tricapped-trigonal prismatic arrangement of the fluorido ligands. [3,4] Compounds with a coordination number of eight of the actinide atom are scarce for fluoridometallates(IV), examples being Li 4 [ [6,11,[14][15][16] In these compounds the complex anions are spatially separated and not connected to each other. For coordination number eight commonly four different ligand arrangements are observed -the ideal polyhedra being either a cube (O h ), a square antiprism (D 4d ), a snub disphenoid (D 2d , Johnson solid J 84 ) or a bicapped trigonal prism (C 2v ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation